2019
DOI: 10.3389/fnmol.2018.00490
|View full text |Cite
|
Sign up to set email alerts
|

Oleoylethanolamide, Neuroinflammation, and Alcohol Abuse

Abstract: Neuroinflammation is a complex process involved in the physiopathology of many central nervous system diseases, including addiction. Alcohol abuse is characterized by induction of peripheral inflammation and neuroinflammation, which hallmark is the activation of innate immunity toll-like receptors 4 (TLR4). In the last years, lipid transmitters have generated attention as modulators of parts of the addictive process. Specifically, the bioactive lipid oleoylethanolamide (OEA), which is an endogenous acylethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 198 publications
5
47
0
Order By: Relevance
“…In fact, GPR119 does not mediate the anorectic effects of OEA . OEA can also interact with another receptor, named as TRPV1, which is also known as the capsaicin receptor . TRPV1 receptors have been reported to exhibit analgesic and thermosensation properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, GPR119 does not mediate the anorectic effects of OEA . OEA can also interact with another receptor, named as TRPV1, which is also known as the capsaicin receptor . TRPV1 receptors have been reported to exhibit analgesic and thermosensation properties.…”
Section: Discussionmentioning
confidence: 99%
“…62 OEA can also interact with another receptor, named as TRPV1, which is also known as the capsaicin receptor. 35,64 TRPV1 receptors have been reported to exhibit analgesic and thermosensation properties. In addition, TRPV1 receptors may be involved in energy homeostasis by regulating food intake and EE.…”
Section: Contribution Of Gpr119 and Trpvi In Satiating Actions Of Omentioning
confidence: 99%
“…For instance, re-feeding of rodents leads to an increase in jejunal C18:1NAE levels, but also leads to a decrease in jejunal C20:4NAE levels (32), despite the notion that both NAEs theoretically share the same biosynthetic machinery. Modulating the NAE-biosynthetic enzymes with appropriate tool compounds should help elucidate the contribution of individual enzymes to the biosynthesis of individual NAEs under various physiological and pathophysiological conditions and could lead to the development of effective therapies for a range of clinical conditions including obesity, inflammation, chronic pain, and addiction (33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that moderate drinking is beneficial to health. For example, it can reduce cardiovascular disease mortality and increase life expectancy (Guzmán et al, 2004;Orio et al, 2019). However, alcohol is also a widely used psychoactive drug which causes many public health problems in our society.…”
Section: Introductionmentioning
confidence: 99%